Enzyme mechanisms for sterol C-methylations - Nes, W.D (Phytochemistry (Oxford), 2003)
The mechanisms by which sterol methyl transferases (SMT) transform olefins into structurally different C-methylated products are complex, prompting over 50 years of intense research. Recent enzymological studies, together with the latest discoveries in the fossil record, functional analyses and gene cloning, establish new insights into the enzymatic mechanisms of sterol C-methylation and form a basis for understanding regulation and evolution of the sterol pathway. These studies suggest that SMTs, originated shortly after life appeared on planet earth. SMTs, including those which ultimately give rise to 24 alpha- and 24 beta-alkyl sterols, align the si(beta)-face pi-electrons of the Delta(24)-double bond with the S-methyl group of AdoMet relative to a set of deprotonation bases in the active site. From the orientation of the conformationally flexible side chain in the SMT Michaelis complex, it has been found that either a single product is formed or cationic intermediates are partitioned into multiple olefins. The product structure and stereochemistry of SMT action is phylogenetically distinct and physiologically significant. SMTs control phytosterol homeostasis and their activity is subject to feedback regulation by specific sterol inserts in the membrane. A unified conceptual framework has been formulated in the steric-electric plug model that posits SMT substrate acceptability on the generation of single or double 24-alkylated side chains, which is the basis for binding order, stereospecificity and product diversity in this class of AdoMet-dependent methyl transferase enzymes. The focus of this review is the mechanism of the C-methylation process which, as discussed, can be altered by point mutations in the enzyme to direct the shape of sterol structure to optimize function.